PENYULUHAN KESEMPATAN KERJA BAGI SDM PENYANDANG DISABILITAS KETENAGAKERJAAN - Santi Djailani; Novita Wahyu Setyawati; Maidani (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
Public transportation activities are developing so rapidly, so that every public transportation business, one of which is rail public transportation, is renovating and improving services from all aspects. In marketing strategy, to increase sales, an important factor that needs to be considered is the level of customer satisfaction. Monitoring customer satisfaction that is carried out properly is a material for conductingaccountable evaluations for decision making related to improving rail services, fulfilling service processes needed by customers, and improving service processes to customers. The purpose of this study is to see the extent to which public service facilities are influenced by the quality of service for commuter line users. In addition, to see how much public service facilities are affected by the quality of service for commuter line users. The method used in this study is a quantitative method using SPSS 21.0 software. In the study, it was found that public services had a significant positive effect on customer satisfaction of commuter line train users, where the higher the public service provided by the commuter line train, the higher customer satisfaction. Rail public service standards have a significant positive effect on customer satisfaction of commuter line train users.Keywords : Customer Quality and Public Service.